Barriers and Facilitators to Optimal Midwife Competence in Normal Delivery Care: Perspectives from Community Health Centers in Padang Pariaman, Indonesia - Elwitri Silvia; Dewi Asmawati; Wiwi Syaptiani (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Midwives are essential healthcare providers for maternal and neonatal health, particularly in normal deliveries. Their competence directly affects the health outcomes of both mothers and newborns. This study aimed to identify the barriers and facilitators influencing midwife competence in providing normal delivery care in Community Health Centers (CHCs) in Gasan Gadang, Padang Pariaman, Indonesia. Methods: A cross-sectional study was conducted among 31 midwives in CHCs in Gasan Gadang, Padang Pariaman, Indonesia. Data were collected using questionnaires assessing midwife competence, workload, work environment, and disciplinary adherence. Descriptive statistics, inferential analysis (Chi-square), and multivariate analysis were performed using SPSS v.16. Results: 61.3% of midwives demonstrated good competence in normal delivery care. A significant association was found between workload and competence (p=0.001). No significant association was observed between the work environment and competence (p=0.149) or between disciplinary adherence and competence (p=0.567). Multivariate analysis revealed that workload had the most significant impact on midwife competence. Conclusion: Workload is a significant factor influencing midwife competence in normal delivery care. Interventions aimed at optimizing workload, such as adequate staffing and resource allocation, are crucial for ensuring competent care and positive health outcomes.